1995
DOI: 10.1103/physreva.52.4678
|View full text |Cite
|
Sign up to set email alerts
|

Electron-impact core excitation ofSF6. II. Generalized oscillator strengths in the S 2pregion

Abstract: The generalized oscillator strengths (GOSs) for discrete and continuum S 2p excitations of SF6 have been derived in the momentum transfer range (K ) of 1 -20 a.u. from the angular variation of the relative differential cross section for inelastic electron scattering. The experimental techniques and data processing procedures used to obtain reliable, absolute GOS values are documented. The GOS results are compared to recent literature results [J. F. Ying, C. P. Mathers, and K. T. Leung, Phys. Rev. A 47, R5 (199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…First, the existing theoretical methods for calculation and interpretation of the X-ray absorption near edge structure may also be applied to ρ 0 , thus addressing the same general scientific questions about local structure and chemical bonding but with spectral information that is independent of (in fact orthogonal to) that provided by XAS. The necessary theoretical generalizations have already been made for calculation of S ( q ,ω) or the full spectrum of ρ l (ω) by real-space full multiple scattering calculations 30 and by approaches based on the Bethe−Salpeter equation. , Work on nondipole contributions to EELS has shown that comparison to molecular-orbital calculations may be used once the correct selection rules are realized, as does more recent work in the NRIXS community. , Simultaneous fits to the independent information provided by the different l -DOS components would be optimal in this context.…”
Section: Nonresonant X-ray Raman Scatteringmentioning
confidence: 99%
“…First, the existing theoretical methods for calculation and interpretation of the X-ray absorption near edge structure may also be applied to ρ 0 , thus addressing the same general scientific questions about local structure and chemical bonding but with spectral information that is independent of (in fact orthogonal to) that provided by XAS. The necessary theoretical generalizations have already been made for calculation of S ( q ,ω) or the full spectrum of ρ l (ω) by real-space full multiple scattering calculations 30 and by approaches based on the Bethe−Salpeter equation. , Work on nondipole contributions to EELS has shown that comparison to molecular-orbital calculations may be used once the correct selection rules are realized, as does more recent work in the NRIXS community. , Simultaneous fits to the independent information provided by the different l -DOS components would be optimal in this context.…”
Section: Nonresonant X-ray Raman Scatteringmentioning
confidence: 99%
“…It manifests directly the atomic wave functions and the dynamics of scattering. Since then, the GOS has received attention from a variety of perspectives: determination of the correct spectral assignment [3], exploring the excitation dynamics [4], probing the intricate nature of the valence-shell and inner-shell electron excitation [5], investigation of the influence of the angular resolution and pressure effects on the position and amplitude of the GOS minima [6], investigation of the GOS ratio [7] and various correlation effects [8][9][10][11], as well as multiple minima [12].…”
Section: Introductionmentioning
confidence: 99%
“…Implicit in this is the extrapolation of the measured data through sometimes the unphysical region [17]. The limiting behavior of the GOS as q 2 → 0 has been a subject of continuing interest because of the difficulty of measuring reliably the electron DCS's for atoms, ions and molecules at and near zero scattering angles [3,14,18]. This difficulty still plagues measurements of the DCS's [19,20], including the most recent measurements of the DCS's [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Note that with the increasing of K 2 , the energy position of the very broad feature observed at the scattering angles of 6°and 8°, i.e., the Bethe ridge, moves to higher energy loss and the corresponding width becomes more diffuse. Such phenomena have also been observed in other molecules such as H 2 O [32] and SF 6 [33]. Furthermore, some features marked as ␣ and ␤ stand out at large scattering angles.…”
Section: Theoretical Methodsmentioning
confidence: 76%